Comparative Study of the Mind - Mahdi Masoudi, Mohammad (International Journal of Psychosocial Rehabilitation, 2019)
The purpose of this study is to compare minds from the point of view of the philosophers and psychologists and finally to arrive at a comprehensive and consistent theory. For this reason, we discussed the mind and examined the function of the mind. On the question of the unity or plurality of the mind and the body, Plato’s and Aristotle’s views on the mind and the body were examined. Mulla Sadra’s theory was then used as the criterion theory in this regard. The result of the study suggests that, from the Sadrian viewpoint, we can clearly reject the psychology that considers the mind to be independent and unconnected entity to the body, as well as the physical and materialist psychologies that deny the mind and assumes all of the manifestations and psychological phenomena related to the physical and mental aspects. He took the middle way, which included neither extreme subjectivism nor pure materialism.